Seismic Vertical Component Effects on the Pathology of a Historical Structure, Xana, Located in Greece - Terzi, Vasiliki; Athanatopoulou, Asimina (Frontiers in Built Environment, 2021)
The present study aims to investigate the effects of the seismic vertical component on the pathology of Xana monument which is a typical caravanserai, constructed circa 1375-1385 and is located in the archeological site of the municipality of Trainapoulis, Greece. The monument’s plan is rectangular and the three-leaf masonry circumferential walls support a hemicylindrical dome constructed by bricks and mortar. The structure consisted of two consecutive parts: one for the travelers and one for the animals. Nowadays, the triangular roof, that covered the structure, and the first part of the monument do not exist. Xana suffers tensile cracks along the interior surface of the dome, a vertical fracture located on the northern wall and vertical tensile cracks located at the openings. A three-dimensional finite element model of the initial state of Xana is constructed. Nonlinear material behavior is taken into account as well as soil-structure interaction effects. An adequate number of near-field earthquake events has been used, taking into account they are related to significant vertical components. The structural seismic analysis is conducted for two cases. The first case refers to the action of the two horizontal-component of ground motions while the second one takes into account the three translational seismic components. The pathology estimation reveals important information concerning the structural effects due to vertical accelerations.